La modelación en la enseñanza y aprendizaje de la matemática del nivel de educación secundaria - González Pasaca, Wilson Alejandro (2024)
A common conception in mathematics teaching practices is that modeling represents an application of mathematical principles. This implies that mathematics is first taught and then the application of such knowledge is sought. However, in the present work, modeling is seen as a teaching method for the construction of mathematical knowledge linked to a context. The objective of the research was to analyze the implementation of modeling in the teaching and learning of mathematics at the secondary education level. For this, the research employed a mixed-methods study; and based on a systematic documentary review of thesis, scientific articles, and books, those works that provide results in relation to the research topic were selected. The main results show that the methodological processes involved in modeling are: the contextualization of content through the presentation of real-world problems; the creation of a mathematical model; problem solving; and validation of results. Likewise, this strategy has a positive influence on the learning and motivation of the students. Consequently, modeling provides students with a unique opportunity to apply mathematical concepts in real, meaningful contexts, thereby promotes critical thinking by challenging students to analyze, evaluate, and solve problems; and in turn stimulates creativity by motivating students to explore different alternatives to address problems. Keywords: mathematics teaching, mathematical modeling, methodological processes, didactic strategy, teaching and learning